A model of perceived business value from social media usage pattern - Suryana, Asep; Risanti, Yuliani Dewi (Manajemen Komunikasi, 2026)
Background: As social media continues to evolve, it gives transformative opportunities for Micro, Small, dan Medium Enterprises (MSME’s), to conduct digital promotion that is not only affordable but also interactive. Purpose: This research aims to explore the patterns of social media utilization among MSME actors in Sumedang Regency, West Java, within the context of an increasingly disruptive digital business environment. Methods: This research use qualitative approach with case study and Focus Group Discussions (FGDs) as the primary method of data collection. There are 15 MSME actors from diverse sectors with varied products and social media practices. In addition, in depth interview were conducted with MSME business owners and officials from the local government division. Results: The findings reveal that social media is leveraged to facilitate communication, expand business networks and widen promotional reach. There are several core functions of social media, including identify construction, information dissemination, entertainment, and public opinion formation. Due to limitation in digital literacy, MSME actors tend to exhibit characteristics of undirected information seekers. Conclusions: Overall, social media is perceived as a strategic tool that can enhance market access, accelerate communication processes and unlock new entrepreneurial opportunities. Implications: These findings emphasize the importance of strengthening digital capabilities and optimizing social media use to improve MSME competitiveness in the disruptive era.